Molecular mechanisms of renal cell carcinoma metastasis and potential targets for therapy - Xinwei Li; Xinwei Li; Wei Xiong; Zhiyong Xiong; Zhiyong Xiong; Xiaoping Zhang; Xiaoping Zhang; Xiaoping Zhang (Frontiers in Cell and Developmental Biology)
Renal cell carcinoma is a common type of cancer, with approximately 30% of patients potentially developing metastatic disease. Some patients with metastatic renal cell carcinoma are found in advanced stages, so the 5-year survival rate for metastatic renal cell carcinoma is only 14%. Currently, there are several drugs available for patients with metastatic renal cell carcinoma, and their overall survival can be extended to nearly 5 years. However, the sensitivity and efficacy of the treatment are still unsatisfactory. New targets and drugs to improve patient prognosis are urgently needed, but these are closely linked to the molecular mechanisms of renal cell carcinoma metastasis. In this review, we present the definition and common molecular mechanisms of metastatic renal cell carcinoma and provide new insights on their potential link to targeted therapies, which may enlighten scientists to develop future targeted therapeutic agents to improve the prognosis of patients with metastatic renal cell carcinoma.